Ethnopharmacological importance and medical applications of Myrothamnus flabellifolius Welw. (Myrothamnaceae)-A review. (24th April 2020) - Erhabor, J.O.; Komakech, R.; Kang, Y.; Tang, M.; Matsabisa, M.G.
Abstract: Ethnopharmacological relevance: Myrothamnus flabellifolius Welw. (resurrection plant) is a desiccant-tolerant, woody, and shrubby plant. It is popularly used as a local medicinal herbal tea in South Africa, other Southern Africa nations, and Central Africa. M. flabellifolius is used in treating several ailments including epilepsy, mental disorder, cough, pain, stroke, shingles, diabetes, hypertension, wounds, asthma, kidneys and chest ailments. Aim of this review: This review focuses on the botanical description, distribution, conservation status, ethnobotany, chemistry and pharmacological properties of M. flabellifolius to spur further research that will promote its sustainable harvesting and commercialization. Material and methods: A literature search on diverse scientific databases, including Google, Google Scholar, Science Direct, PubMed, Scopus, theses, dissertations and ethnobotanical textbooks, were conducted. Results: The conducted search reveals that M. flabellifolius has many traditional uses that can be categorized into infectious diseases, Well-being, respiratory, inflammation, wound and kidney ailments. M. flabellifolius is a natural caffeine-free medicinal herbal tea reported to have antioxidant, anticancer, antiviral, antidiabetic and antimicrobial properties. Toxicological tests on M. flabellifolius were found scarce with gaps in genotoxicological and in vivo studies. Essential oils and isolated compounds were identified from M. flabellifolius with biological activities such as anticancer, antiinflammation, antimicrobial, antiarthritic, antiulcer, antioxidant and antiviral properties. Conclusion: It is envisaged that the current review will add value to more scientific research on M. flabellifolius and enhance/promote the increased interest in the sustainable commercialization of M. flabellifolius herbal tea as well as lead to the validation of unverified ethnobotanical claims. Graphical abstract: Image 1